Effect of co-solvent on structural and morphological properties of ZnO aerogel prepared by a modified sol-gel process. Issue 1 (18th April 2014) - Meddouri, Malaaz; Djouadi, Djamel; Chelouche, Azeddine; Touam, Tahar; Chergui, Abdelhamid
Abstract : Nanocrystalline zinc oxide (ZnO) aerogel powders were synthesized using a modified sol-gel process. Ethanol, acetone and methanol were used as supercritical drying fluids. Effects of co-solvent on morphological and structural properties were investigated. The as prepared powders were characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The XRD results show that drying in solvents mixture affects the crystalline quality and acts as a compression agent by exerting stress on the lattice parameters. SEM micrographs demonstrate that co-solvent plays a key role in controlling ZnO nucleation and favors the particles agglomeration with increasing the pressure and the temperature. The EDAX analysis shows that the obtained ZnO nanopowder with ethanol and acetone as co-solvent is pure with different stoichiometries (an excess of oxygen (O) with ethanol and zinc (Zn) atoms with acetone). However, when methanol is used as supercritical drying fluid, the obtained nanopowder contains an excess of carbon (C) atoms. FTIR absorption bands are more intense for aerogel synthesized by drying in methanol indicating the presence of more C-H bounds responsible of the low rate agglomeration of the ZnO crystallites.